Cuentas por cobrar en la cooperativa de transporte de carga "6 de octubre" en la ciudad de Babahoyo, periodo 2019-2020. - Santillán Cadena, Edison Edwin (2022)
Cargo Transport Cooperative "October 6" of the city of Babahoyo, Province of Los Ríos, is an institution that provides services to users, collaborators and clients at the national level of shipments or transfer of cargo, and like other companies of services, this requires activities not only in its services, but also works with records of financial movements that the company has in order to have a better administrative vision of it and be able to make decisions that allow it to expand and stay within the tertiary sector along with other service companies nationwide. The administration of accounts receivable is developed based on compliance with the policies established by the collection department in relation to the analysis, study and evaluation carried out by the professional regarding the economic situation of the users of these services offered; If the professional in charge does not comply with these conditions of monitoring, evaluation of the economic financial capacity and follow-up control of the client, it will lead to problems due to non-payment of accounts receivable at the time of carrying out their activities, causing economic deficiency in the cooperative. cargo transport. This work is in charge of carrying out an analysis of the rotations of accounts receivable to determine if the respective collection processes are being carried out and to avoid any type of inconvenience that ends up creating an economic deficiency within the aforementioned transport service company applying the techniques necessary analytics to find the values of those indicators that offer the answer.